2009
DOI: 10.1007/s12588-009-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of ABS nano composite reinforced by nano sized alumina particulates

Abstract: To study the effect of addition of alumina nano sized particles in ABS thermoplastic composites, ABS was reinforced by nano sized alumina particles through melt compounding. The microstructure, thermal stability, dynamic mechanical, static mechanical properties and tribological analysis of the developed nano composite were investigated in detail. The dispersion morphology of alumina particles in the ABS polymer matrix was investigated through SEM. Addition of the alumina into the ABS matrix increased the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The transition around 20°C appeared, corresponding to the glass transition temperature of partially crystalline PP, which is similar with other results . The highest peak around 115°C in the curves corresponds to the glass transition temperature of ABS . Two glass transition temperatures and the difference for each curve were listed in Table , which indicated the change of intermolecular force and compatibility.…”
Section: Resultssupporting
confidence: 87%
“…The transition around 20°C appeared, corresponding to the glass transition temperature of partially crystalline PP, which is similar with other results . The highest peak around 115°C in the curves corresponds to the glass transition temperature of ABS . Two glass transition temperatures and the difference for each curve were listed in Table , which indicated the change of intermolecular force and compatibility.…”
Section: Resultssupporting
confidence: 87%
“…Various inorganic nanofillers are being reinforced into polymer matrix to improve stiffness as well as to reduce the cost . Vivek Kumar et al synthesized ABS composites reinforced with nanoalumina and reported that incorporation of nanoalumina enhances thermal stability and also improves mechanical properties such as tensile strength and modulus with reduction in impact strength and elongation. Bonda et al evaluated the thermal properties of nanofly ash reinforced ABS Composites and observed that addition of smaller sized fly ash particles resulted in improved performance of ABS/NFS composites.…”
Section: Introductionmentioning
confidence: 99%
“…In the PE matrix, C3B was finely dispersed at 2 wt % and with a high density at 5 wt %, as illustrated in Figures 2(a) and 2(b). e earlier research [35][36][37] explored the mechanical characteristics of treated materials in terms of their tensile, flexural, impact, and Shore D hardness measurements, as well as their thermal properties (DSC, TGA, and dynamic analysis).…”
Section: Production Of Nanocomposites Of Polyethylene/c3b/eacmentioning
confidence: 99%